Immunomodulatory Activity of Kasumba Turate (Carthamus tinctorius L.) Extract Against Non-Specific and Specific Immune Responses in Mice - Arini Fadhilah; Anisa Dwi Parwati; Cita Hanif Muflihah; Arifah Sri Wahyuni (Universitas Muhammadiyah Surakarta, 2023)
Immunomodulators are compounds that can regulate the immune system with the objective of normalizing or helping to optimize the immune system. People tend to back to nature by utilizing various plants to be used as medicine, one of which is kasumba turate (Carthamus tinctorius L.) which is thought to be efficacious as an immunomodulator in increasing the activity and capacity of macrophages. This study aims to determine the immunomodulatory activity of kasumba turate ethanol (CTEE) extract against non-specific and specific immune responses in mice. Non-specific immune response tests using the carbon clearance method were carried out on mice with 3 dose ratings. Specific immune response tests were carried out by the hemagglutination test method to determine antibody titers. The results of the carbon clearance test showed that the CTEE dose 50 mg/KgBW was a moderate immunostimulant with a phagocytic index of 1.41, while doses of 100 and 200 mg/KgBW were strong immunostimulants with phagocytic index of 1.57 and 1.82 respectively. While the results of the hemagglutination test method, the antibody titers value is determined from the highest serum dilution value that still indicates hemagglutination. The results show an increase in humoral immune response with the highest primary and secondary antibody titer values of 1:256 and 1:1024 for doses of 100 mg/KgBW, and 1:512 and 1:1024 for doses of 200 mg/KgBW. Phytochemical screening results of CTEE proved to contain alkaloid group compounds, flavonoids, saponins, tannins and triterpenoids. Based on the results obtained, it was concluded that the administration of CTEE showed immunostimulant activity.